Enhancing Pre-service Teachers’ Noticing: A Learning Environment about Fraction Concept - Pedro Ivars (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2021)
Professional noticing allows teachers to recognise important events in a classroom and give effective responses using their knowledge. Hence developing this competence in teacher training programs is an issue in the Mathematics Education field. In this study, we present the design of a learning environment about the part-whole meaning of fraction to develop pre-service primary school teachers’ noticing of students’ mathematical thinking. The learning environment is designed around three tasks (vignettes) that pre-service teachers have to analyse using knowledge from research on mathematics education provided as a students’ hypothetical learning trajectory. Eighty-five pre-service teachers participated in this learning environment. Results allows us to characterise the enhancement of pre-service teacher noticing through looking at the changes in the discourse generated in the three tasks.